DYNAMICS OF ILLEGAL LOGGING .FROM THE SOEHARTO REGIME TO REGIONAL AUTONOMY - Herman Hidayat (Jurnal Kependudukan Indonesia, 2007)
Deforestation which occurred in Indonesia is very serious. In the end ofSoeharto government it registered annually about 2-2.5 million hectares. It rapidly increased until reaches 2.5-3 million hectares in the era of reformation (1998-2004 ). The most contribution upon deforestation is illegal logging practices in many districts. Big actors of illegal logging utilize local people as tools; made collusion and corruption with government bureaucrats in central as well local and the lack oflaw enforcement are becoming driving factors for illegal logging. In contrast, current government efforts to crush illegal logging and their networks still considered not yet maximal, and it effects upon government revenues from forestry sector considered still very low. This paper discusses definition, conceptual, scholars' comment on illegal logging practices, driving factors and its implication upon forestry industries and local people.Keywords: illegal logging, implication of deforestation, forestry industry and local people.